PENGARUH RULE OF LAW DAN PEMAHAMAN AKUNTANSI TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH - Ayem, Sri; Oktaviani (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2024)
This research aims to determine the influence of the rule of law and understanding of accounting on Regional Financial Management Accountability. The population in this study were all BKAD employees of Gunungkidul Regency. Sampling was carried out using purposive sampling, namely employees related to the financial management report of BKAD Gunungkidul Regency. The data analysis used is the path coefficient value. The results of this research show that the rule of law has a positive effect on accountability. Understanding accounting has no effect on accountability. The implication in this research is that the rule of law is an important variable in influencing the accountability of regional financial management in Gunungkidul Regency. The rule of law is a tool to monitor and encourage the creation of correct, transparent and fair government management in accordance with the rules of law.